NILAI PENDIDIKAN DALAM CERPEN ANAK PADA MAJALAH UMMI - Kalfia, Rosi; Bahardur, Iswadi; Andheska, harry (Pendidikan Bahasa Indonesia, 2014)
This researeh is relid on the moral values, social, social volues, intelektual values and religious values. The purpose of the researeh is to deseribe educational values of choldren shortstories in mogazine ummi from the result of the researeh we can concllude that children short stories in magazine ummi heve moral, social, intelektual, and religios values. Moral values contain keeping promise end gorgeus. Intelektual values contain keping promiet the wise end gorgeus. Intelektual values contain eritical thinking. Logical thinking, engcreative thingking critical thingking is that the children consee clearly and fast the wrong things. Logical thingking is that the children can see the relationship between problems fast. Creative thingking is that the chil dren can find something new from researeh and experiment they do. Social values inelude patience, mutual assistance, sy mpaty, hospitaling andrespectfulness. Meanwhile the religious values are thanking to Allah Swt and ashing for help.